Microstructure and Phase Chemistry of Vacuum Induction Melting Fabricated-Equimolar AlCoCrFeNi HEA During Spinodal Dissolution Annealing - Hussain, Mudassar; Mohd Najib, Abdillah Sani; Fadil, Nor Akmal; Abu Bakar , Tuty Asma (International Journal of Integrated Engineering, 2024)
The quinary equimolar AlCoCrFeNi high entropy alloy (HEA) as a promising candidate for advanced engineering applications has grasped significant consideration in recent years due to its ability to undergo tailorable microstructure transformation and properties. The transient understanding of elemental distribution and response to the cooling rate during dissolution annealing and binodal decomposition are still required to evaluate. The present study investigates variations in phase chemistry and microstructure during dissolution annealing at 1h and 16h at 800˚C (air cooled) by FESEM-EDS mapping and XRD analysis. Secondly, to identify binodal decomposition in samples annealed at 1250oC for 20h is revealed at different cooling rates (water quenching and furnace cooling) employing FESEM-EDS. Remarkable binodal decomposition was witnessed with distinct phase composition and phase boundaries during slow cooling, while thin interfacial face centered cubic (FCC) phase separation occurred in a rapidly cooled sample. However, heating at 800˚C for 1h and 16h revealed modulated microstructure with rearrangements in the chemical composition of phases compared to cast microstructure. Al-Ni rich dendritic region and Cr-Fe rich interdendritic region interdiffusion during dissolution annealing at 800oC with Ni and Cr cross mobilisation. However, Co remains in uniform distribution in both regions. It confirms microstructure tailor ability and variance in engineering applicability of quinary equimolar AlCoCrFeNi high entropy alloy with different thermal treatments.